Implementasi Standar Proses dan Dampak Kognitifnya dalam Pembelajaran Matematika oleh Guru yang Tersertifikasi dan Belum Tersertifikasi - Ari Wibowo Hikmal (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2019)
Abstract:The problems due to the finding of the tendency of teachers to carry out the teaching and learning process are not in accordance with the learning plan that has been made and the discrepancies between learning devices in this case the learning implementation plan (RPP) made by the teacher with the ongoing teaching and learning process. This type of research is descriptive qualitative which aims to describe the implementation of process standards (planning, implementation, assessment) and their cognitive impact on Mathematics learning by teachers of Makassar 21 Middle School that are certified and not yet certified. The results show that (1) standard process implementation in Mathematics learning by teachers certified in (a) Mathematics learning planning by HASMTK and ROSMTK subjects is in the Good assessment category, (b) implementation of Mathematics learning activities by HASMTK subjects and ROSMTK in the Very Good assessment category, (c) assessment of Mathematics learning activities by HASMTK and ROSMTK subjects in the Very Good assessment category. (2) student learning achievement taught by certified teachers in Mathematics learning (a) HASMTK subjects are in the High category, but the average value of students taught by the subject does not meet classical standards. (b) the subject of ROSMTK is in the High category and the average value of students taught by the subject meets classical standards. (3) the implementation of process standards in Mathematics learning by teachers who have not been certified in (a) Mathematics learning planning by ELMTK subjects is in the Good rating category, (b) the implementation of Mathematics learning activities by ELMTK subjects is in the Very Good assessment category, (c) the assessment of Mathematics learning activities by ELMTK subjects is in the Very Good assessment category. (4) learning achievement of students taught by teachers who have not been certified in Mathematics learning, by ELMTK subjects are in the High category. however, the average value of students taught by the subject does not meet classical standardsAbstrak:Adapun permasalahan karena adanya ditemukan kecenderungan guru  dalam melakukan proses belajar mengajar tidak sesuai dengan rencana pembelajaran yang telah dibuatnya serta ketidaksesuaian antara perangkat pembelajaran dalam hal ini rencana pelaksanaan pembelajaran (RPP) yang dibuat guru dengan proses belajar mengajar yang sedang berlangsung. Jenis penelitian ini adalah deskriptif kualitatif yang bertujuan untuk mendeskripsikan implementasi standar proses (perencanaan, pelaksanaan, penilaian) dan dampak kogniifnya dalam pembelajaran Matematika oleh guru SMP Negeri 21 Makassar yang tersertifikasi dan belum tersertifikasi.. Hasil penelitian menunjukkan bahwa (1) implementasi standar proses dalam pembelajaran Matematika oleh guru yang tersertifikasi pada (a) perencanaan pembelajaran Matematika  oleh subjek HASMTK dan ROSMTK berada dalam kategori penilaian Baik, (b) pelaksanaan kegiatan pembelajaran Matematika oleh subjek HASMTK dan ROSMTK berada dalam kategori penilaian Amat Baik, (c) penilaian kegiatan pembelajaran Matematika oleh subjek HASMTK dan ROSMTK berada dalam kategori penilaian Amat Baik. (2) prestasi belajar siswa yang diajar oleh guru tersertifikasi dalam pembelajaran Matematika (a) subjek HASMTK berada dalam kategori Tinggi, akan tetapi nilai rata-rata peserta didik yang diajar oleh subjek tidak memenuhi standar klasikal. (b) subjek ROSMTK berada dalam kategori Tinggi dan nilai rata-rata peserta didik yang diajar oleh subjek memenuhi standar klasikal. (3) implementasi standar proses dalam pembelajaran Matematika oleh guru yang belum tersertifikasi pada (a) perencanaan pembelajaran Matematika oleh subjek ELMTK berada dalam kategori penilaian Baik, (b) pelaksanaan kegiatan pembelajaran Matematika oleh subjek ELMTK berada dalam kategori penilaian Amat Baik, (c) penilaian kegiatan pembelajaran Matematika oleh subjek ELMTK berada dalam kategori penilaian Amat Baik. (4) prestasi belajar siswa yang diajar oleh guru yang belum tersertifikasi dalam pembelajaran Matematika, oleh subjek ELMTK berada dalam kategori Tinggi. akan tetapi nilai rata-rata peserta didik yang diajar oleh subjek tidak memenuhi standar klasikal.